Awareness and Experience of using off-label Drugs by Doctors and Pharmacists in Libya - Taher, Monia Ramadan; Abdelrahman, Riad Mohammed; Suliman, Mohsen Hussein; Musa, Taha Hussein (British Journal of Healthcare and Medical Research, 2025)
Background: The off-label use refers to the administration of an authorized medicinal product in a manner not specified in its official labeling. This practice raises significant legal, ethical, and safety concerns, particularly given its widespread prevalence. However, many healthcare professionals have limited awareness of the definition, scope, and clinical implications of off-label drug use. This study aimed to assess the knowledge and perceptions of pharmacists and physicians regarding off-label drug use in Libya. Methods: A prospective, questionnaire-based cross-sectional study was conducted among doctors and pharmacists in Libya. A total of 374 licensed Libyan healthcare professionals were targeted between September 2024 and March 2025. Results: 160 participants were included in the final analysis. Most respondents were female (n=106, 66%), with pharmacists and clinical pharmacists constituting the majority (37% and 23%, respectively). Additionally, 131 participants (82%) were affiliated with tertiary care settings, and most had 1-4 years of work experience (n=110, 69%). Only 69 respondents (44%) were aware of the correct definition of off-label drugs, particularly pharmacists and clinical pharmacists (p=0.02 and p=0.002, respectively). Off-label prescriptions were reported by 63 respondents (43%), with a higher prevalence among males (p=0.002). A significant proportion of participants were unaware of any institutional or national policies regarding off- label prescribing (64% and 72%, respectively). Concerns about the efficacy and safety of off-label prescribing were prevalent (61% and 68%, respectively). Notably, 62% of respondents reported encountering adverse drug reactions related to off-label prescriptions. Furthermore, 131 participants (82%) emphasized the importance of pharmacist involvement in off-label drug use decisions. Conclusion: These findings underscore the need for targeted educational interventions and formal regulatory guidelines to promote safer prescribing practices and improve patient outcomes, particularly among physicians engaged in off-label drug use.